A new Stein estimator for the zero‐inflated negative binomial regression model. (6th May 2022) - Akram, Muhammad Nauman; Abonazel, Mohamed R.; Amin, Muhammad; Kibria, B. M. Golam; Afzal, Nimra
Abstract: The Zero‐inflated negative binomial (ZINB) regression models are mainly applied for count data that shows over‐dispersion and extra zeros. Multicollinearity is considered to be a significant problem in the estimation of parameters in the ZINB regression model. Thus, in order to alleviate the serious effects of multicollinearity, a new estimator is proposed which is called ZINB Stein estimator (ZINBSE). We also proposed various biasing parameters for the ZINBSE. A theoretical comparison is also conducted with some existing estimators in the literature. A Monte Carlo simulation study has been considered in order to judge the superiority of the proposed and other estimators, where the estimated mean squared error and mean absolute error are the evaluation criterion. An empirical application is also considered for illustration purposes. Based on the simulation and application results, it is observed that the new ZINBSE with proposed biasing parameters are superior over the other competitors' estimators.